Genetic Plasticity of V Genes Under Somatic Hypermutation: Statistical Analyses Using a New Resampling-Based Methodology - Oprea, Mihaela; Kepler, Thomas B. (Genome Research, 1999)
Evidence for somatic hypermutation of immunoglobulin genes has been observed in all of the species in which immunoglobulins have been found. Previous studies have suggested that codon usage in immunoglobulin variable (V) region genes is such that the sequence-specificity of somatic hypermutation results in greater mutability in complementarity-determining regions of the gene than in the framework regions. We have developed a new resampling-based methodology to explore genetic plasticity in individual Vgenes and in V gene families in a statistically meaningful way. We determine what factors contribute to this mutability difference and characterize the strength of selection for this effect. We find that although the codon usage in immunoglobulin V genes renders them distinct among translationally equivalent sequences with random codon usage, they are nevertheless not optimal in this regard. We find that the mutability patterns in a number of species are similar to those we find for human sequences. Interestingly, sheep sequences show extremely strong mutability differences, consistent with the role of somatic hypermutation in the diversification of primary antibody repertoire in these animals. Human TCR V βsequences resemble immunoglobulin in mutability pattern, suggesting one of several alternatives, that hypermutation is functionally operating in TCR, that it was once operating in TCR or in the common precursor of TCR and immunoglobulin, or that the hypermutation mechanism has evolved to exploit the codon usage in immunoglobulin (and fortuitously, TCR) rather than vice-versa. Our findings provide support to the hypothesis that somatic hypermutation appeared very early in the phylogeny of immune systems, that it is, to a large extent, shared between species, and that it makes an essential contribution to the generation of the antibody repertoire.
10.1101/gr.9.12.1294